Konvergensi IFRS terhadap Manajemen Laba (Studi Konseptual) - Restu Argarinjani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Accounting standards are guidelines used in accounting practice. The existence of profit management cases carried out by several large companies in the United States such as Enron, WorldCom, and so on triggered the creation of a new accounting standard that is applied globally, namely IFRS. IFRS was developed by the IASB with the aim that this international standard can minimize profit management practices in addition to improving the quality of financial statements. Profit management practices are one of the topics that are often debated because this practice can reduce the credibility of financial statements and can add bias in financial statements. However, when viewed from the point of view of management who wants to display the company's performance and condition remains good, it is also not a wrong thing. This profit management practice will actually not be negative if in managing the profits of a company using accounting methods that are allowed by generally accepted Financial Accounting Standards. This article is designed to describe the convergence of IFRS in Indonesia and its impact on profit management.